Text-fig. A3. a: Leaf morphotype 1 Tebano MSF SG 049. b: Leaf morphotype 2 Oriolo MSF 631. c: Leaf morphotype 3 Oriolo MSF n.n. d, f: Leaf morphotype 4. d: Oriolo MSF 891. e: Oriolo MSF 856. f: Oriolo MSF 858. g: Leaf morphotype 5 Oriolo MSF 783. h: Leaf morphotype 6 Oriolo MSF 952. i: Leaf morphotype 7 Oriolo MSF 862. j, l: Leaf morphotype 8. j: Oriolo MSF 912. k: Oriolo MSF 662. l: Oriolo MSF 662-1. m: Leaf morphotype 9 Oriolo MSF 715. n: Leaf morphotype 10 Oriolo MSF 716. o: Leaf morphotype 11, overview and detail of margin Oriolo MSF 880. p–z: Various rosaceous leaves/ leaflets. p: Oriolo MSF 943. q: Oriolo MSF 890. r: Oriolo MSF 950. s: Oriolo MSF 958. t: Oriolo MSF 966 aff. Sorbus. u: Oriolo MSF 956. v: Oriolo MSF 961. w: Oriolo MSF 962. x: Oriolo MSF 874. y: Oriolo MSF 883. z: Oriolo MSF 960. in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. A3. a: Leaf morphotype 1 Tebano MSF SG 049. b: Leaf morphotype 2 Oriolo MSF 631. c: Leaf morphotype 3 Oriolo MSF n.n. d, f: Leaf morphotype 4. d: Oriolo MSF 891. e: Oriolo MSF 856. f: Oriolo MSF 858. g: Leaf morphotype 5 Oriolo MSF 783. h: Leaf morphotype 6 Oriolo MSF 952. i: Leaf morphotype 7 Oriolo MSF 862. j, l: Leaf morphotype 8. j: Oriolo MSF 912. k: Oriolo MSF 662. l: Oriolo MSF 662-1. m: Leaf morphotype 9 Oriolo MSF 715. n: Leaf morphotype 10 Oriolo MSF 716. o: Leaf morphotype 11, overview and detail of margin Oriolo MSF 880. p–z: Various rosaceous leaves/ leaflets. p: Oriolo MSF 943. q: Oriolo MSF 890. r: Oriolo MSF 950. s: Oriolo MSF 958. t: Oriolo MSF 966 aff. Sorbus. u: Oriolo MSF 956. v: Oriolo MSF 961. w: Oriolo MSF 962. x: Oriolo MSF 874. y: Oriolo MSF 883. z: Oriolo MSF 960. Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 260, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867